MOTIVASI, PRESTASI BELAJAR, DAN PELATIHAN KERJA KAITANNYA TERHADAP KREATIVITAS SISWA - Wardi, Rika (UNIVERSITAS NEGERI SURABAYA, 2013)
This study aims to determine the size of the influences of motivation, academic achievement, and job training on students creativity (Prakerin) for 3rd State Vocational School of Pamekasan. This study was using a quantitative approach with the level of associative forms of causal explanation. Population of this study was students from grade XII that take Prakerin class in academic year 2012-2013. Sample was taken by using purposive sampling for grade XII who follow the industry practice (Prakerin) in Production and Services Unit (UPJ) School with total of 68 students. Technique of data collection was using questionnaires technique, documentations, and observation sheets. Data were analyzed using multiple linear regression analysis. The results show that creativity is influenced by motivation, academic achievement and job training by 44.9 % while the remaining 55.1 % are influenced by factors other than the variable motivation, achievement and training. Keywords: motivation, learning achievement, job training, students creativity